"Creative city" as a brand – the case of łódź. Issue 1 (2nd January 2016) - Brzozowska, Blanka
Abstract : The aim of the paper is to discuss the case of Polish city Łódź. Łódź flourished as the textile industry city since the second half of the 19th century. That changed after the Poland's transition to a market economy. In the new situation, the city began to decline, both economically and socially. In 2012 the city authorities have adopted the Łódź Brand Management Strategy for the Years 2010–2016 and Integrated Development Strategy for Łódź 2020+ . The essential element of both strategies is to apply the idea of creative industries. The motto "Łódź – City of Creative Industries" not only determines the direction of the current development of the city, but also it was the basis for applying for the title of "European Capital of Culture". The paper presents the case of Łódź from the perspective of the official strategies adopted by the city authorities, and at the same time from the perspective of grassroots activities undertaken by residents that fit, sometimes unintentionally, in the brand strategy of Łódź as the city of creative industries.